Penguatan Program Padat Karya Produksi U-Ditch Sebagai Strategi Peningkatan Kesejahteraan Masyarakat Berpenghasilan Rendah (MBR) Di Kelurahan Tambak Wedi Kecamatan Kenjeran Kota Surabaya - Rohma, Nur Faizatur; Azizah, Siti (Jurnal PUBLIQUE, 2024)
This study discusses the Labor-Intensive U-Ditch Production Program as a strategy to improve the welfare of low-income communities (MBR) in Tambak Wedi Village, Kenjeran District, Surabaya, and collaboration between stakeholders in its implementation. The method used is qualitative with a case study approach. The subjects of the study included program workers, the Bina Marga Agency, and CV Nahila Perkasa Mandiri selected through purposive sampling. Data collection techniques include interviews, observations, and documentation, analyzed through data reduction, presentation, and verification with source triangulation to ensure validity. The results of the study show that this program has succeeded in creating jobs, increasing income, providing access to health services, developing new skills, and strengthening social relations in the community. Collaboration between stakeholders is effective, where the Surabaya government acts as an initiator and facilitator, the Water Resources and Bina Marga Agency manages and supervises the program, sub-district heads and village heads help with socialization, the community actively participates as workers, and CV Nahila Perkasa Mandiri provides U-Ditch materials. This program not only has an impact on improving economic welfare, but also contributes to strengthening social relations and developing community capacity.